Effects of Basic Needs and Course Self-Efficacy on Agentic Engagement Among Pre-Service Chinese Teachers - Tianlin Xie; Fong Peng Chew (SAGE Open)
The widespread promotion of Chinese in the world is closely linked to the training of pre-service Chinese teachers in China. Agentic engagement in pre-service Chinese teachers’ training study is particularly important for their professional ability and career development. Supported by self-determination theory and social cognitive theory, this study seeks to investigate the process through which the satisfaction of basic psychological needs such as autonomy, competence, and relatedness, as well as course self-efficacy, as motivating factors, influence agentic engagement to help pre-service Chinese teachers actively participate in course activities and make full preparation for the future Chinese teaching career. A total of 201 pre-service Chinese teachers from six public liberal arts universities in Beijing, China, participated in this study. The results from structural equation modeling indicate that (1) the need for autonomy, competence, and relatedness directly predicts course self-efficacy and agentic engagement; (2) Course self-efficacy has a direct positive effect on agentic engagement; (3) Course self-efficacy partially mediates the relationship between the three basic needs and agentic engagement, respectively. This study emphasizes the need to address the three fundamental needs and sense of efficacy of pre-service Chinese teachers in fostering and motivating their agentic engagement and considers implications for research and teaching at the higher education level.